Comparative Analysis of Concrete QTO Using BIM and Conventional on XYZ Project - Rizki Adithya Wibowo; Putri Ayu Dwiyana; Junita Eka Susanti (Universitas Islam Raden Rahmat, Malang, 2025)
The rapid advancement of technology in the construction sector has encouraged the integration of digital modeling systems such as Building Information Modeling (BIM) to improve project efficiency and accuracy. This study analyzes the implementation of BIM using Autodesk Revit 2025 in the integrated design and build construction of the XYZ Project. The objective is to compare the Quantity Take Off (QTO) results between the BIM method and conventional concrete calculation for column and beam structures, as well as to evaluate the resulting cost differences. A quantitative comparative approach was employed by modeling the structure using Revit and manually calculating the quantities through conventional methods. The results show that both methods produced the same concrete volume for columns (891.6 m³), while for beams, the BIM method produced 1,104.59 m³ compared to 1,227.47 m³ from conventional calculations, yielding a difference of 122.88 m³ (11.12%) equivalent to IDR 294,831,618.37 in cost savings. The study concludes that BIM provides higher precision and reduces potential material waste, supporting more efficient budgeting and sustainable construction management.